Flexibilizaç\~ao fiscal: Novas evidências e desafios - Sérgio Wulff Gobetti; Rodrigo Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This discussion paper intends to complement the analyzes carried out in Gobetti (2015), updating the diagnosis of the development of fiscal balances of the Brazilian public sector from the new series of GDP released by IBGE and statistics "above the line" that incorporate regional level of government. Additionally, it uses several indicators to better characterize the recent expansion (or flexibility) phase of the Brazilian fiscal policy (2011-2014) compared to previous periods and, finally, analyzes the sustainability of public spending trajectory in different scenarios.
Keywords: E62; E65; H62; 330; fiscal expansion; structural balance; fiscal impulse; discritionary fiscal effort